ANALISIS MUTASI DAN KOMPETENSI KOMUNIKASI TERHADAP PRESTASI KERJA PEGAWAI - Panji Pramuditha (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
This study aims to determine and analyze the presence or absence of the analysis of mutations and communication competence on the employee performance at sekretariat daerah provinsi jawa barat both partially and simultaneously, given the difficulty of managing human resources in order to continue to contribute and work well, in order to support the activities at Sekretariat Daerah Provinsi Jawa Barat which resulted in the need to improve employee performance. This research uses descriptive verification method. Primary data in this study were obtained from the results of a questionnaire distributed directly to 60 respondents of Sekretariat Daerah Provinsi Jawa Barat, while secondary data are obtained from data from Sekretariat Daerah Provinsi Jawa Barat for the period of 2019. The analytical method used is multiple linear regression analysis using the SPSS 21 Software application and testing the hypothesis of the t test and statistical test of the f test. The results show that employee performance is significantly affected by mutations and communication competence by partial 0.811; employee performance is significantly affected by mutations and communication competence simultaneously shows a positive correlation, and in the category of very strong relationships, means that the better the mutations and communication competence, the better employee performance.